(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
نبين في هذا البحث توزع الفحوم الهيدروجينية البترولية في الرسوبيات الشاطئية لمدينة جبلة، حيث تم تحديد التراكيز الكلية لهذه الفحوم الهيدروجينية في 63 عينة رسوبية سطحية مأخوذة من سبعة مواقع شاطئية على شواطئ جبلة خلال الفترة الممتدة ما بين 2000/10/30 و15/12/2001 وباستخدام تقانة مطيافية الفلورة في مجال الأشعة فوق البنفسجية(UV-F) معتمدين الكرايزين(chrysene) كمركب عياري. تراوحت تراكيز الفحوم الهيدروجينية بين 0.008-0.647μg/g من الوزن الجاف، ولوحظ بأن أعلى التراكيز سجلت في المحطة ST4 (مرفأ الصيد) نتيجة النشاط البشري في المرفأ. وكانت التراكيز في المحطتين ST1 وST1a متقاربة حيث مصدر تلوثهما ما تحمله مياه المسيل النهري دائم الجريان(نهر الشراشير) تبين هذه الدراسة أن تراكيز الفحوم الهيدروجينية البترولية في المواقع المدروسة ضمن حدود مقبولة بالمقارنة مع مناطق أخرى من المتوسط. This study shows the distribution of petroleum hydrocarbons in tidal sediments of Jableh coast.The total concentrations of petroleum hydrocarbons (PHCs) were determined in (63) surface samples of sediments taken from seven tidal sites in Jableh coast, during the period (30/10/2000 - 15/12/2001). using the technique of flourospectrometry (UV-F) and chrysene as a standard compound. The concentration of (PHCs) ranged between 0.008-0.647μg/g of dry weight. The highest concentrations were registered in ST4 (fishing port), which indicate that this region is affected by human activities in the port. Concentrations in ST1, ST2 were almost similarl, due to the main source the permanently running water of Alshrasheer river. This study indicates that the concentration of petroleum hydrocarbons in those sites are low compared with some other regions along the Mediterranean sea.